IMPACT OF IRON OXIDE ON CAPSAICIN ALKALOID PRODUCTION FROM Capsicum annuum L. IN VITRO - E. H. Jassim; R. K. Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The chili pepper plant Capsicum annuum L. is used in processed foods and pharmaceuticals given the importance of Capsaicin; it has been produced through cell cultures of chili pepper obtained from a media known as Murashige and Skoog (MS), which is supplied by the best concentration1.5 and 0.3 mg/L of 2,4-Dichlorophenoxyacetic acid (2,4-D) and kinetin (kin.), respectively, gave highest fresh and dry weights of callus, reaching (368.06,29.40) mg respectively which was significantly different from other treatments. When determining the alkaloid compound capsaicin by HPLC, Its amount in the callus was found to be 3.8 μg/g after being treated with a nano dose of 0 mg/L. an increase of 1.5 fold over the quantity in the leaves of the plant growing in the field, which reached 2.5 μg/g. In order to increase the synthesis of active compound studied stimulated by iron oxide nanoparticles at concentrations (0, 2, 4, 6, 8, and 10) mg/L, the findings indicated that 6 mg/L caused a highly significant increase in Capsaicin, reaching 6.2 μg/g by the amount 1.6 fold compared to 3.8 μg/g in the treatment free the nanocatalyst. While the concentration of 6 mg/L achieved a 2.5-fold increase in its presence in the chili pepper intact leaf sample, the results show that Fe3O4NPs were effective in stimulating the accumulation of capsaicin compound.